RACIAL AND SEXUAL HARASSMENT DEPICTED IN “THEIR EYES WERE WATCHING GOD” - Abdirakhmonova, Gulnora (Educational Research in Universal Sciences, 2023)
Zora Neale Hurston’s Their Eyes Were Watching God has garnered mixed reviews for its portrayal of the African American struggle. While some of her male contemporaries viewed the novel as an oversimplification of racial issues, a closer examination of the text reveals otherwise. This abstract delves into Hurston’s nuanced depiction of the despair faced not only by African Americans, but also by women. Hurston adeptly captures the complexities of race, sexuality and gender without resorting to the anger and hostility found in the works of many of her male African American peers, including Richard Wright. By portraying the female protagonist’s skin color, language, and character, Hurston creates an authentic image of African American women in the early 1900s. Her use of African American vernacular gives Janie Crawford a distinct voice, despite society’s efforts to silence her. Through an analysis of the context, narrative, and language, the work argues that Their Eyes Were Watching God is not simply a tragic love story, but a masterful representation of race, gender, sexuality and class issues in America during that time period.